You can't.
x4 + y4 is irreducible.
It's (x+yi^1.5)(x+yi^0.5)(x-yi^1.5)(x-yi^0.5). You use the equation x^2-y^2=(x+y)(x-y) and x^2+y^2=(x+yi)(x-yi).
*Edit This IS reducible.
X^4+Y^4=X^4+Y^4+2X^2Y^2 -2X^2Y^2 I add and minus 2X^2Y^2 so the value stays the same.
X^4+Y^4+2X^2Y^2=(X^2+Y^2)^2
So it equals to (X^2+Y^2)^2-2X^2Y^2.
Then, we factor using difference of squares.
(X^2+Y^2)^2-2X^2Y^2=(X^2+Y^2+sqrt2 XY)(X^2+Y^2-sqrt2 XY)
*Note the XY is not included in the sqrt sign
x4 - 4x3 - 12x2 -32x + 64 (x - 4)(x + 2)(x + 2)(x - 4)
(x - 3)(x + 1)(x + 2)(x + 4)
Greatest common factor of x4 and x3 is x3.
(y - 4)(y + 4)(y^2 + 16)
(x^2 + 1)(x^2 - 4x + 13)
x2 + y4 + x4 +y2 = x6 + y6unless you know what x and y are.* * * * *x2 + y4 + x4 + y2 ??I don't believe that this expression can be factorised or otherwise simplified.It certainly does not equal x6 + y6,for all x and all y:for example, if x = y = 1, thenx2 + y4 + x4 + y2 = 4, whilstx6 + y6 = 2;thus, they are two manifestly unequal quantities.
(x2 + y2)(x + y)(x - y) = x4 - y4.
(x4 + y4)/(x + y) = Quotient = x3 - x2y + xy2 - y3 Remainder = - 2y4/(x+y) So, x3 - x2y + xy2 - y3 - 2y4/(x+y)
sqrt(100x4y4) = sqrt(100)*sqrt(x4)*sqrt(y4) = 10*x2*y2
18xy is the GCF of 72x2y and 18xy
(x + y)2 = x2 + 2xy + y2 So x2 + y2 = (x + y)2 - 2xy = a2 - 2b Then (x2 + y2)2 = x4 + 2x2y2 + y4 So x4 + y4 = (x2 + y2)2 - 2x2y2 = (a2 - 2b)2 - 2b2 = a4 - 4a2b + 4b2 - 2b2 = a4 - 4a2b + 2b2
(y^2 + 8)(y^2 + 2)
(x+y)4 = (x2+2xy+y2)2 = x4+4x3y+6x2y2+4xy3+y4
2y4(16 - x4) = 2y4 (4 + x2)(4 - x2) = 2y4(4 + x2)(2 + x)(2 - x)
It is: 1(x4+4y8) and can't be factored any further
y4.
x4 - 4x3 - 12x2 -32x + 64 (x - 4)(x + 2)(x + 2)(x - 4)